Fitting Biochars and Activated Carbons from Residues of the Olive Oil Industry as Supports of Fe- Catalysts for the Heterogeneous Fenton-Like Treatment of Simulated Olive Mill Wastewater - Bruno M. Esteves; Sergio Morales-Torres; Francisco J. Maldonado-Hódar; Luis M. Madeira (Nanomaterials, 2020)
A series of biochars and activated carbons (ACs) was prepared combining carbonization and physical or chemical activation of cheap and abundant residues of the olive oil industry. These materials were used as Fe-support to develop low-cost catalysts for the heterogeneous Fenton-like oxidation of simulated olive mill wastewater (OMW), the highly pollutant effluent generated by this agroindustry. Commercial ACs were also used as reference. All catalysts prepared were extensively characterized and results related with their performances in the catalytic wet peroxide oxidation (CWPO). Results showed a linear relationship of the textural properties of the catalysts with the adsorptive and catalytic performance, as well as the preferential adsorption and degradation of some phenolic compounds (caffeic and gallic acids) by specific interactions with the catalysts’ surface. Despite the best performance of catalysts developed using commercial supports, those prepared from agro-industrial residues present some advantages, including a smaller catalyst deactivation by iron leaching. CWPO results show that catalysts from physically activated olive stones are the most promising materials, reaching total organic carbon and toxicity reductions of 35% and 60%, respectively, as well an efficient use of H2O2, comparable with those obtained using commercial supports. This approach showed that the optimized treatment of this type of residues will allow their integration in the circular economic process of the olive oil production.